Lingkungan Pendidikan dalam Perspektif Al-Qur’an - Supian Munawar; Syamsul Maarief; Badruzaman Badruzaman; Endi Suhendi (CV. Alim's Publishing, 2026)
The research in this paper aims to explore the concepts and principles of the educational environment from the perspective of the Qur'an and Hadith using a tafsir tarbawi (educational exegesis) approach. The developmental dynamics of human potential, both spiritual and intellectual, do not occur in a vacuum but are heavily influenced by environmental factors (educational ecology). By employing textual, thematic, and contextual analysis methods on several key verses such as QS. Al-Alaq: 1-5, QS. At-Tahrim: 6, QS. Luqman: 13-19, QS. Al-Kahfi: 66-70, and QS. Al-Hujurat: 13 this study maps the Islamic educational ecosystem into several primary domains. The results of the analysis indicate that the Qur'an constructs the educational environment as an integrative macro-systemic unity, comprising the domestic family environment (as a fortress for moral and creedal protection), the formal academic school/pesantren environment (as a space for teacher-student etiquette and ethics), and the socio-communal environment (as an arena for egalitarian multicultural inclusivity). Furthermore, this study formulates five fundamental paradigms of Islamic educational ecology: the integralistic, tawhid (monotheistic), humanistic-egalitarian, gradual-systemic, and transformational-emancipatory paradigms. This theoretical reconstruction corrects Western secular empiricism while simultaneously providing a holistic foundation for educators in managing an educational environment that aligns with divine revelation values and the demands of modern civilization.